MEMBANGUN INSTITUSIONAL REPOSITORY PERPUSTAKAAN PERGURUAN TINGGI : Persoalan dan Tahapannya - setiawan setiawan (FPPTI Jawa Tengah, 2019)
A form of Information Technology advances in digital library, a change from manual system to digital system, with one of its embodiment is an institutional repository. Institutional repository is a form of service that is built by college libraries in an effort to facilitate management and dissemination of digital materials. However, not all universities are able to make its institutional repository based library-based, especially for collections of scientific work (Thesis and Dissertation) because many problems faced by the college library in terms of funding, human resources and other devices. This study can be used as a reference for universities that plan to build an institutional repository, in terms of understanding problems faced and the stages in building the institutional repository. Keywords : digital library, institusional repository